Blue Growth and Green Decisions: Financing Sustainable Fisheries Entrepreneurship - Raghu, Mr. Tanna; Murthy , Dr. Kudumula Venkata Ramana; Mandala, Dr. Gangu Naidu (International Journal of Accounting and Economics Studies, 2025)
The article analyzes the fisheries entrepreneurship in Andhra Pradesh in terms of its investment planning and decision-making in the context of Sustainable Blue Economy finance. A structured questionnaire was administered to 120 entrepreneurs at small, mid- and large-scale business in the Visakhapatnam Port region, evaluating ten dimensions, such as environmental priority, knowledge of innovative finance instruments, and confidence in risk-management, on a five-point Likert scale. ANOVA with one way revealed that large-scale operators had significantly higher means on the prioritisation of the environment (F(2,117)=50.016, p
Keywords: Blue Economy Finance; Fisheries Entrepreneurs; Investment Decision-Making